EFEKTIVITAS PELATIHAN KOMUNIKASI POSITIF TERHADAP KEMAMPUAN KOMUNIKASI POSITIF GURU DI TK IT TOP KIDS SOKARAJA PURWOKERTO - Hapsari Melati Ismi; Yuki Widiasari (Universitas Muhammadiyah Purwokerto, 2018)
This study aims to improve Master's positive communication skills in early childhood. Subjects in this study were 12 teachers in PAUD Top Kids Sokaraja district. The research was conducted through experimental method. Subjects were subjected to two positive meetings of positive communication training, with the total number of meetings being 8 hours. Data analysis was done by visual inspection technique, on 4 measurement of baseline stage, treatment stage 1, treatment stage 2, and follow-up stage. The results of the study prove a significant increase in the positive communication skills of the subject, based on the scale of positive communication skills. In the baseline phase, the average subject has a positive communication skill score of 33.67 (Enough). In the treatment phase 1, it increased to 38.08 (Enough). In the third measurement, ie in the treatment phase 2, increased to 44.41 (Good). In the follow-up phase it increased to 48.08 (Good). Keywords: positive communication skills, communication training, kindergarten teacher